Ho Chi Minh’s ideology on education: Content and meaning - Ninh, Nguyen Dinh (Linguistics and Culture Review, 2023)
Education plays a particularly important role, not only contributing to the development of human personality but also a driving force for the development of society. Therefore, most countries in the world consider investment in education as an investment in the future and define educational development. Ho Chi Minh left the Vietnamese people an invaluable theoretical legacy on the fundamental issues of the Vietnamese revolution, including the ideology of religion expressed in his views on the role, purpose, content, and methods of education are very profound, so far still have the same theoretical and practical meaning.